Application of Behavioral Counseling with Techniques to Improve the Behavior of Role Playing can Receive Advice of Others Sciences Grade X 3 SMA Negeri 1 Singaraja - Gangga Pitaloka; I Ketut Dharsana (International Conference on Technology and Educational Science)
This research aims to suggestions from other's students of class X of Sciences 3 at SMAN 1 Singaraja. Type of research was quasi-experimental research design "pretest-posttest control group design." .this research sample member 32 students who have been high to receive advice from other people. The data used are questionnaire self-methods of data analysis methods using ttest and tacount 15 141 ttab 1.67 with (5,141 > 1.67) Ho and Ha rejected accepted results of research demonstrating that there is the influence of counseling role playing technique's grade X SCIENCES 3 of Singaraja Senior High School 1.